Prospective Elementary Teachers’ Expereinces on Mini Research Projects on A Design Research Course - Putra, Zetra Hainul; Aljarrah, Ayman; Kartikowati, Rr. Sri; Faizah, Hasnah (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2024)
Design research is an emerging research method in mathematics education, but it has a potential to be applied in elementary education. To support prospective elementary teachers’ competences in designing learning instruction for elementary schools, we develop a design research course in the elementary teacher education study program in the University of Riau, Pekanbaru, Indonesia. The course has been delivered to prospective elementary teachers since 2023 by the first author. The course consists of lectures about various educational design research approach and mini research projects on designing a learning instruction for a specific topic for elementary school students after the mid-term exam. We examine prospective elementary teachers’ experiences on the mini research projects to evaluate effectiveness of the design research course. The results of this study could be used to develop the design research course for the future.